Clinical and laboratory parameters, risk factors predisposing to the development of priapism in sickle cell patients. Issue 1 (January 2020) - Alkindi, Salam; Almufargi, Said S; Pathare, Anil
Although sickle cell disease is very common in Oman, priapism is a relatively rare complication of this disease. This study was aimed to identify the clinical and laboratory risk factors that predispose sickle cell disease patients to priapism. In a retrospective, case-control study, data on 21 male sickle cell disease patients, with priapism, were compared to 20 age and sex-matched sickle cell disease patients without priapism from the hospital medical records. Specifically, the demographical, hematological, biochemical, and clinical parameters including complications attributable to priapism were studied. Means for continuous measures and independent t-test were used to evaluate the association between the parameter studied and the occurrence of priapism. Priapism occurrence was associated with low basal hemoglobin (Hb), along with an increase in other parameters such as white blood cell count (WBC) ( P = 0.010), platelet count ( P = 0.001), reticulocyte count ( P < 0.001), mean corpuscular volume (MCV) ( P < 0.001), and mean corpuscular hemoglobin (MCH) ( P < 0.001). Biochemical laboratory parameters revealed an association with an increased total bilirubin ( P < 0.001). Patients with priapism were more likely to have acute chest syndrome, stroke, pulmonary hypertension, asplenia ( P = 0.006), gallbladder stones, and consequently cholecystectomy. Blood exchange and Penile aspiration were the most frequent medical therapies ( P = 0.010 and P < 0.001 respectively). Patients with sickle cell disease who presented with priapism were young adults with low Hb, high WBC's, platelets, reticulocytes, MCV, MCH, bilirubin, and LDH. These findings suggest an association of priapism with increased hemolysis. Impact statement: Sickle cell disease is prevalent throughout the world with a 5.8% incidence of sickle cell trait among the Omani population, yet priapism was a relatively rare complication. Penile erection and detumescence are complex physiological processes, which require a delicate neurohormonal and cardiovascular response. In this cohort, young SCD patients developed priapism with a low incidence of complications. These patients had high WBCs, platelets, bilirubin, LDH, and reticulocytes with low hemoglobin as compared to controls, suggesting an increased hemolytic process. Favorable outcome was dependent on early intervention, with almost half of these patients needing surgical intervention.